Mechanical, Interfacial, and Fracture Characteristics of Poly (lactic acid) and Moringa oleifera Fiber Composites - Islam, Muhammad R.; Nadia, Isa; Ahmad N., Yahaya; Beg, M. D. H.; R. M., Yunus (Wiley, 2018)
Three different processing techniques, extrusion, injection, and compression, were followed to fabricate poly (lactic acid) (PLA) and Moringa oleifera fiber (MOF) based composites. Chopped fibers of length 3–5 mm were used for the extrusion followed by injection molding, whereas long-length fibers (~100 mm) were used for compression molding process. For compression molding, long-length fibers were spread in single and double layers. The interfacial shear strength of the composites was evaluated by fiber pull-out testing. Composites were characterized for fracture behavior and mechanical properties. Additionally, surface morphology was also observed by scanning electron microscopy, whereas crystalline properties were evaluated by X-ray diffraction analysis. Analyses revealed that compression molding with double layers of long-length fibers reinforcement showed better properties than other samples. Tensile strengths of extruded and compression processed samples (double-layered) were 75.5 and 81.1 MPa, which are approximately 33% and 44% higher respectively than neat PLA (56.5 MPa). The crack generation of PLA during applied load was observed and found eliminated for the double-layered sample processed via compression molding. It was found that compression molding with double layer can be considered as easy and less time-consuming method for composite preparation, with nearly 8 wt.% of less fiber consumption compared with extrusion/injection molding.